Dilemmas of sustainable urban development a view from practice - Metzger, Jonathan 1978-; Lindblad, Jenny (New York, NY Routledge, 2020)
"Dilemmas of Sustainable Urban Development offers valuable insights into a difficult line of work whose practice inevitably requires a confrontation with fundamental conflicts between divergent goals, and therefore also demands difficult choices and compromises. With contributions from leading academics and expert practitioners, this book provides readers with diverse international case studies which highlight and examine the concrete challenges of practicing sustainable urban development. The examples in this book touch upon all aspects of sustainable urban development work, from City Hall to the local park. All of the cases unfold in their own specific contexts under particular circumstances-but from each one of them there are general lessons that can be used to inform practice. This book is essential reading for anyone who is active as a student, researcher, or practitioner in the field of urban development"--
Includes bibliographical references and index.
Keywords: Sustainable urban development; City planning -- Environmental aspects